Fostering Academic Resilience: The Efficacy of Solution-Focused Brief Counseling (SFBC) in Alleviating Test Anxiety Among High-Achieving Adolescents - Souza, Felipe; Costa, Bruna; Akhtar, Shazia (Research Psychologie, Orientation et Conseil, 2025)
Test anxiety is a significant barrier to academic success, particularly among high-achieving adolescents who face high academic pressures. The impact of test anxiety on students’ performance and psychological well-being necessitates effective interventions. Solution-Focused Brief Counseling (SFBC), a short-term, goal-oriented approach, has shown promise in addressing various psychological concerns, yet its specific efficacy in alleviating test anxiety among high-achieving adolescents remains under-explored. This study aims to investigate the effectiveness of SFBC in reducing test anxiety and enhancing academic resilience in this population. A quasi-experimental design was employed, with 60 high-achieving adolescents randomly assigned to either an experimental group (SFBC intervention) or a control group. Pretest and posttest measures were taken using the Test Anxiety Inventory (TAI) and the Academic Resilience Scale (ARS). The experimental group received five SFBC sessions, while the control group received no intervention. Results indicated that the SFBC intervention significantly reduced test anxiety and enhanced academic resilience among the experimental group. The mean TAI score decreased significantly, and the ARS score increased, indicating improved coping strategies and greater academic perseverance.